Heating Has No Effect on the Net Protein Utilisation from Egg Whites in Rats. (26th February 2017) - Matsuoka, Ryosuke; Takahashi, Yayoi; Kimura, Mamoru; Masuda, Yasunobu; Kunou, Masaaki
Abstract : Egg whites (EW) are a good source of protein; however, they are typically heated prior to consumption. Therefore, we investigated the effects of different heating conditions on the protein utilisation rate of EW. Male Sprague-Dawley rats (n = 36, 198 ± 1  g) were divided into six groups and fed American Institute of Nutrition-76 chow containing unheated EW, soft-boiled EW, boiled EW, milk whey protein, soybean protein, or no protein over a 10-day period using pair-feeding. Urine and faeces were sampled daily beginning on day 5 to measure nitrogen content and the net protein utilisation (NPU) rate. The soybean protein group had a significantly lower level of food intake and was thus excluded from subsequent analyses. The NPU value was similar among the unheated, soft-boiled, and boiled EW groups (97.5 ± 0.4, 96.5 ± 0.1, and 96.5 ± 0.7, resp.). The EW group values were significantly higher than the whey group values (90.5 ± 1.0 ). These results show that EW serve as a good source of protein, irrespective of heating.